(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
This paper proposes a novel stochastic optimization approach named optimization by morphological filter (OMF) for solving the combined economic emission dispatch (CEED) problem with the valve point effect and multiple equality and inequality constraints. Four standard test systems, with and without transmission losses, are optimized to demonstrate the performance of OMF. Comparing the experimental results with various methods reported in the literature proves the high quality of OMF for solving CEED problems for small and large-scale systems.